High ebullitive, millennial‐aged greenhouse gas emissions from thermokarst expansion of peatland lakes in boreal western Canada. Issue 2 (26th December 2022) - Kuhn, McKenzie A.; Schmidt, Megan; Heffernan, Liam; Stührenberg, Jördis; Knorr, Klaus‐Holger; Estop‐Aragonés, Cristian; Broder, Tanja; Gonzalez Moguel, Regina; Douglas, Peter M. J.; Olefeldt, David
Abstract: Methane (CH4 ) and carbon dioxide (CO2 ) emissions from small peatland lakes may be highly sensitive to climate warming and thermokarst expansion caused by permafrost thaw. We studied effects of thermokarst expansion on ebullitive CH4 and CO2 fluxes and diffusive CH4 fluxes from a peatland thaw lake in boreal western Canada. Ebullitive CH4 fluxes from the thaw edge (236 ± 61 mg CH4 m −2 d −1 ) were double and quadruple that of the stable lake edge and center, respectively. Modeled diffusive CH4 fluxes did not differ between the thawing and stable edges ( 50 mg CH4 m −2 d −1 ) but were double that of the center. Radiocarbon ( 14 C) analysis of CH4 and CO2 bubbles from the thaw edge was older ( 1211 and 1420 14 C yr BP) than from the stable edge and the center (modern to 102 and 50 14 C yr BP, respectively). Incubations indicated that deep, old peat sediment was more labile along the thaw edge than in the center. While our study suggested increase CH4 emissions partly derived from millennial‐aged carbon along the thaw edge, accounting for these emissions only increased the estimated total lake CH4 emissions by 10%, which is a much smaller contribution than measured from thermokarst lakes in yedoma regions. Our study suggests that it is important to account for landscape history and lake types when studying the processes that govern the sensitivity of lake greenhouse gas emissions to climate change.